Derfor har vi brug for paradigmer - Jeppesen Kragh, Kirsten; Schøsler, Lene (Ny forskning i grammatik, 2016)
Based on previous studies on verbs of perception in French and Italian, this study claims that the notion of paradigm is useful for the understanding of grammatical structure. Our case-study concerns the status of Modern French voir in the paradigms of presentation and of progressivity.